SISTEM INTEGRASI PADI TERNAK UNTUK MEWUJUDKAN KEDAULATAN PANGAN - DINI YULIANI (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
Rice as a staple food source of Indonesian people is still a top priority. However, efforts to increase rice production faced a variety of problems such as a decrease in the productivity of paddy fields due to the lack of organic matter. In addition to rice, meat is quite important food. To fulfill the need of domestic meat portion should be imported. This is an opportunity for the development of cattle breeding business in Indonesia. Crop Livestock Systems Integration (CLS) is one alternative in increasing the production of rice, meat, and dairy while improving the welfare of farmers and ranchers. There are three main technology components CLS namely: 1). Rice cultivation technology, 2). Livestock farming technology, and 3). Straw and compost processing technology. Technology components that can be integrated synergistically, then CLS development done by the institutional approach. CLS program aims to optimize the utilization of local resources such as the use of straw as livestock feed and cow manure can be processed into organic fertilizer that is very helpful to improve the nutrients that plants need so no waste is wasted (Zero waste). Utilization of cow manure was processed into liquid and solid organic fertilizer, is expected to serve as a source of additional income for farmers. Compost and liquid fertilizer and is expected to improve the fertility of agricultural land. CLS program was initiated in conjunction with a program of integrated crop management (ICM). In addition, the development of farming systems approach CLS needs to be done through farmer groups to facilitate agricultural extension, livestock grains technology adoption, and government aid channel. The advantage of the rice-livestock integration pattern that is the utilization of crop residues as a source of animal feed, utilizing livestock manure as fertilizer, creating new jobs in rural areas, and increase community participation in creating a competitive agribusiness, environmental friendly and independent. CLS constraints in achieving food security among farmers groups working mechanism was not going well, utilization of collective cages was not optimal, mentoring and coaching process was not effective because the cattle were scattered locations, the use of manure has not been entrenched among rice farmers, and the application of CLS conducted throughout provinces in Indonesia and there was no apparent progress. Repair CLS for the future should focus on the region so that large-scale production centers and significant impact on population growth and productivity of livestock. Livestock waste treatment close to the location of the rice to minimize transport costs so as to create zero waste and integrated farming systems to achieve food sovereignty.